A Prospective Study of Early Radiation Associated Cardiac Toxicity Following Neoadjuvant Chemoradiation for Distal Esophageal Cancer - Burke, Aidan M.; Yeh, Celine; Kim, Sunnie; Bergquist, Peter; Krishnan, Pranay; Barac, Ana; Srichai, Monvadi B.; Unger, Keith (Frontiers in Oncology, 2020)
Purpose: This study aimed to prospectively evaluate the early effects of radiation on cardiac structure and function following neoadjuvant chemoradiation for distal esophageal cancer. Methods and Materials: Patients with non-metastatic esophageal cancer who were suitable for tri-modality therapy with concurrent chemoradiotherapy followed by esophagectomy were enrolled. Cardiac magnetic resonance imaging (CMR) was obtained at baseline and 3–5 months following completion of chemoradiation. Standardized myocardial segmentation was used to identify regions on post-treatment CMR with new T2 signal or late gadolinium enhancement (LGE). Pre and post-treatment cardiac function was assessed with quantitative end points including left ventricle end-systolic volume (LSESV). Serum biomarkers of cardiac damage including troponin I, CRP, and BNP were collected at baseline and time of follow-up CMR. Results: A total of 11 patients were enrolled from 2016 to 2018. Patients had clinical stage T2 (18%) and T3 (82%) disease with clinical N0 (27%) and N1 (73%) nodal stage. All patients completed baseline CMR and completed chemoradiotherapy. One patient did not complete follow-up CMR or serum biomarkers and was excluded from the analysis. The median time from completion of chemoradiation to follow-up CMR was 3.9 months. Three out of 10 patients (30%) developed new structural findings of myocardial fibrosis and/or reversible ischemia involving the basal and mid-inferior and inferoseptal walls. In these three patients, the LVESV was significantly increased from baseline following radiation. There were no differences in other quantitative end points or serum biomarkers between the patients with myocardial damage and those without. Conclusions: Our study is the first to our knowledge to prospectively demonstrate radiation associated structural and functional heart damage as early as 3 months following neoadjuvant chemoradiation for distal esophageal cancer. Given the early onset of this subclinical heart damage, strategies should be developed to identify patients at risk for future clinically significant heart toxicity.